1982
DOI: 10.1126/science.7063860
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and Adipocyte Abnormalities in Offspring of Rats Undernourished During Pregnancy

Abstract: Pregnant rats underfed in the first 2 weeks of gestation had offspring with normal body weight at birth and weaning. However, starting at about 5 weeks of age the male offspring became hyperphagic and gained more weight than the controls. The female offspring did not overeat and did not become obese. Both male and female progeny showed increased fat cell size as adults. In males the epididymal and retroperitoneal fat pads were significantly enlarged nd adipocytes in these pads were hypertrophied. In females an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
106
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(114 citation statements)
references
References 12 publications
6
106
2
Order By: Relevance
“…28 However, as shown by other studies, this is a situation that may change if the animals were challenged with a high fat diet in postnatal life. 23,24 In humans, the data relating to programming of obesity is also somewhat inconclusive. Studies of young adult men and middle-aged women exposed to intrauterine famine during the Dutch Hunger Winter of 1944 indicate that obesity may be in part determined through nutritional programming in early to mid-gestation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 However, as shown by other studies, this is a situation that may change if the animals were challenged with a high fat diet in postnatal life. 23,24 In humans, the data relating to programming of obesity is also somewhat inconclusive. Studies of young adult men and middle-aged women exposed to intrauterine famine during the Dutch Hunger Winter of 1944 indicate that obesity may be in part determined through nutritional programming in early to mid-gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of offspring fed low protein (LP) diets indicate that they may develop increased central fat deposits in early adulthood, 22 but that this effect largely depends on the feeding of a high fat diet. 23,24 We have most recently shown that when offered a choice of food sources, female offspring of rats fed LP diets throughout pregnancy exhibit an increased preference for a high fat diet. 25 In general, the feeding behaviour of young adult rats is altered by exposure to prenatal LP diets, with hypophagia noted when a low fat diet is provided, contrasting with hyperphagia when allowed to self-select macronutrients.…”
Section: Introductionmentioning
confidence: 99%
“…Those who reported being born or conceived outside Philadelphia (n ¼ 91) were excluded from the study, leaving 578 respondents -305 females (mean age ¼ 16. 6 Association of temperature variables and weight Table 1 shows Pearson correlations of environmental temperature during the intrauterine period with the BMI Z-score in adolescence. These analyses were conducted separately for the four groups (gender; ethnic group).…”
Section: Resultsmentioning
confidence: 99%
“…These findings have also been replicated in animal studies. 6,7 These effects are found not only in the offspring of severely malnourished pregnant women, but also in the case of chronic maternal malnutrition due to poverty. 8 Observed links between obesity in adolescence and adulthood and environmental factors include a possible effect of environmental temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Saastamoinen et al (2010) found that undernourished larvae of an East African butterfly (Bicyclus anynana) had more strongly developed thoracic musculature after pupation, enabling them to fly more strongly as adults and potentially to reach more favourable environments. When pregnant mother rats (Rattus norvegicus) were given restricted diets, their offspring were smaller when they were born, but if these offspring were then given plentiful food they became much more obese than the offspring of mothers given an unrestricted diet (Jones and Friedman, 1982). This observation was followed by further extensive work on rats in many laboratories.…”
Section: Conditional Plasticitymentioning
confidence: 97%